Analisis Kontrak Syariah Dalam E-Commerce: Studi Terhadap Akad Murabahah dan Salam di Era Digital - Muhamad Ibnu Afrelian; Chamdini Putri; Khufyah Robe'nur (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
The development of e-commerce presents significant opportunities for Muslims to engage in digital transactions that align with Islamic legal principles. This study aims to analyse the application of Shariah-compliant contracts, specifically murabahah and salam, in digital transactions and identify the challenges faced in their implementation. Using a descriptive-analytical approach, this research examines the validity of these contracts in e-commerce based on fiqh al-muamalat, DSN-MUI fatwas, and maqasid al-shariah. The findings reveal that murabahah and salam contracts are highly adaptable to e-commerce due to their emphasis on transparency and fairness. However, several key challenges were identified, including the potential for gharar caused by inaccurate product descriptions, the contentious validity of digital ijab and qabul, and the risk of riba in instalment-based payment systems. Proposed solutions include strengthening regulations tailored to Shariah-compliant e-commerce platforms, educating consumers and business actors on Shariah-compliant contracts, and providing more transparent transaction mechanisms to minimise gharar. This study concludes that implementing Shariah-compliant contracts in e-commerce aligns strongly with maqasid al-shariah, particularly in safeguarding wealth and ensuring justice for all parties involved.